Congenital Mid Ureteric Valve Stenosis Revisited: Case Report and Review of the Literature - Elifranji, Mohammed; Elkadahi, Abderrahman; Charles, Adrian; Abbas, Tariq O. (Frontiers in Pediatrics, 2019)
Congenital mid ureteric valve (MUV) stenosis is a very rare entity. Definitive preoperative diagnosis is clinically challenging, and most patients are misdiagnosed preoperatively. Intraoperative identification is therefore very important. Curative treatment consists of excision of the involved ureteric segment and anastomosis. This report describes the clinical findings in a patient with congenital mid ureteric valve stenosis, including radiological and histological workup and operative management. Routine intraoperative retrograde pyelography is important in the diagnosis of such rare pathologies.